EFFECTS OF SILICA FERTILIZATION AND IRRIGATION FREQUENCY ON MUNG BEAN YIELD AND QUALITY - Annisa Afifah Putri; Salsabila Putri; Fiky Yulianto Wicaksono; Yuyun Yuwariah (UIN Sunan Gunung Djati Bandung, 2026)
Climate change and increasing water scarcity have intensified drought stress, reducing mung bean (Vigna radiata L.) yield and seed quality. Silica fertilization has gained attention as a strategy to enhance plant tolerance to water limited conditions and improve crop productivity. This study systematically reviewed the effects of silica fertilization and irrigation frequency on mung bean yield and quality using the PRISMA 2020 framework. Literature was collected from major scientific databases, and 68 eligible studies published between 2010 and 2026 were selected for qualitative synthesis. The reviewed studies consistently showed that reduced irrigation frequency decreased growth, physiological performance, yield, and grain quality. In contrast, silica fertilization improved water status, photosynthetic efficiency, antioxidant activity, nutrient uptake, and drought tolerance. Evidence from mung bean and related legume crops demonstrated that silica application enhanced pod formation, seed weight, biomass accumulation, and yield stability under water deficit conditions. The benefits of silica became more pronounced as water availability declined, indicating a complementary relationship between silica fertilization and irrigation management. Overall, integrating silica fertilization with optimized irrigation scheduling offers a promising approach to improve yield, maintain seed quality, enhance water use efficiency, and support sustainable mung bean production under drought prone environments.